Pengaruh Kualitas Produk, Persepsi Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Porte Pizza Cengkareng - Ramjaya, Farhan Sukma Saputra; Tuti, Meylani (Indonesian Journal Publisher, 2024)
The purpose of this study is to examine the impact of product quality, price perception, and service quality on customer satisfaction at Porte Pizza Cengkareng. This research employed purposive sampling, with a total sample size of 175 respondents. Data analysis was conducted using PLS version 3.0 software and structural equation modeling (SEM) to assess the validity and reliability of the questionnaire administered to respondents. The study focused on three variables within the service marketing mix: product quality, price perception, and service quality. The findings reveal that product quality and service quality have a positive and significant effect on customer satisfaction, while price perception does not have a significant effect. This suggests that although price perception varies among consumers, customer satisfaction is more influenced by the quality of the product and the service provided. Therefore, to enhance customer satisfaction, management is advised to pay greater attention to pricing policies while continuously improving product and service quality. Further research is recommended to explore other factors that may contribute to customer satisfaction, providing a more comprehensive perspective for marketing strategies within the restaurant sector.